Death matters: victimization by particle matter from coal fired power plants in the US, a green criminological view - Lynch, Michael J. (Critical criminology, 2015)
The present study examines deaths and diseases associated with pollution from coal fired power plants (CFPPs) and compares the volume of those deaths and diseases to deaths and injuries associated with street crimes. This comparison illustrates that the single form of pollution studied here - CFPP small particle pollution - causes more deaths in the US than homicides and deserves additional criminological attention. We frame our examination of CFPP deaths and injuries in the corporate crime and green criminological literatures, and explore CFPP pollution as an example of corporate environmental violence. The widespread nature of CFPP violence justifies focusing greater criminological attention on this issue, including the development of policies for remedying pollution, which is now a ubiquitous problem with severe health consequences.